Synthesis, characterization and application of Au-198 nanoparticles as radiotracer for industrial applications. (May 2016) - Goswami, Sunil; Pant, H.J.; Biswal, Jayashree; Samantray, J.S.; Sharma, V.K.; Dash, Ashutosh
Abstract: This paper describes synthesis and characterization of radioactive gold nanoparticles ( 198 Au-NPs), and explores their utility as a radiotracer for tracing an aqueous phase in a continuous laboratory-scale bubble column at ambient conditions. The performance of the 198 Au-NPs as a radiotracer was compared with the results obtained with a conventional radiotracer i.e. bromine-82 ( 82 Br) as ammonium bromide and found to be identical. A tank-in-series with backmixing model (TISBM) was used to simulate the RTDs of the aqueous phase and characterize flow in the bubble column. Highlights: 198 Au-NPs were used as radiotracer for tracing aqueous phase. The RTD of the aqueous phase was measured using 198 Au-NPs and 82 Br radiotracers. The performance of 198 Au-NPs as radiotracer was compared and validated. Tank-in-series with backmixing model was used to simulate the measured RTDs.